Delineasi Potensi Perpanjangan Sesar Probolinggo Berdasarkan Respon Anomali Gravitasi Hibrid - Noor Efendi; M. Aryono Adhi; Muhamad Syirojudin; Supriyadi (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This research aimed to delineate the potential extension of the Probolinggo Fault based on hybrid gravity anomaly responses to minimize uncertainties in earthquake disaster mitigation information. The method employed integrates primary terrestrial gravity data from field measurements (72 points) with secondary GGMPlus-SRTM2gravity 2018 satellite data using the collocated cokriging technique. Analysis was conducted using regional-residual anomaly separation via Band Pass Filter, alongside the application of First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) methods to identify structural lineaments. The results show that the hybrid gravity anomaly distribution ranges from -14 mGal to  17  mGal,  representing  the  density  variations  of  Argopuro  and  Lamongan volcanic rocks. Fault lineament delineation was identified over approximately 22 km with a West-East orientation, traversing from Liprak Kidul to Betektaman. Based on an SVD value evaluation showing parity between the hanging wall and footwall (averaging 0.25 mGal/m²), this structure is identified as a strike-slip fault. The study concludes that indications of a westward fault extension beyond the boundaries previously established by Pusgen were found. The use of hybrid data proved to provide optimal spatial resolution in bridging information gaps regarding subsurface structures in areas covered by Quaternary volcanic materials.  Keywords: Delineation, FHD, Hybrid Gravity, Probolinggo Fault, Derivative